Strategi Pengembangan Usaha Pisang Cavendish Pada UD Istana Banana di Desa Pilanggede Kecamatan Balen Kabupaten Bojonegoro - Yulia Khoirun Nisa'; Moh. Yusuf Dawud; Noor Djohar (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Demand for banana commodities in Indonesia is relatively high, especially as an ingredient for food diversification. Judging from per capita consumption, bananas are consumed the most, with an average consumption of 24.71 grams/capita/day. Besides high domestic demand, bananas have high potential and competitiveness in the international market. The value of banana exports in Indonesia has increased by 42.81% from 2021. Throughout 2022, Indonesia has exported 22,112.98 tonnes of bananas to several countries, such as Malaysia, Singapore, and China. However, requests from these countries have not been met by Indonesia (Coordinating Ministry for the Economy of the Republic of Indonesia, 2020). Demand for exports of horticultural commodities, especially bananas, is relatively high but cannot yet be met. This means that the amount of banana production available is still insufficient to meet the community's needs and export of banana commodities. This research aims to determine internal and external factors, appropriate business development strategies, and priority strategies to be implemented at UD Istana Banana. The study was conducted at UD Istana Banana in Bojonegoro Regency in December 2023. Based on the results of the data analysis, the IFE Matrix (Internal Factor Evaluation) got a total score of 3.25, and the EFE Matrix (External Factor Evaluation) got a total score of 2.85. So, in the Internal External (IE) matrix, the company's position is in quadrant IV, which means the company's position is in growth and development. Furthermore, in the SWOT analysis, ten alternative strategies were obtained, and based on the QSPM analysis, it showed that the alternative strategy to develop the business by expanding partnerships and establishing good relationships with work partners and consumers received the highest score with a value of 5.89 which was the priority strategy at UD Istana Banana.